Impact of intestinal colonization by Gram-negative bacteria on the incidence of bloodstream infections and lethality in critically ill neonates - Isadora Caixeta da Silveira Ferreira; Ralciane de Paula Menezes; Thiago Alves de Jesus; Izabella Clara de Brito Machado; Mallu Santos Mendonça Lopes; Aline Diulia Costa; Lúcio Borges de Araújo; Denise Von Dolinger de Brito Röder (Elsevier, 2023)
Background: Early detection of antimicrobial-resistant microorganisms is crucial to prevent subsequent invasive infections and contain their spread in the Neonatal Intensive Care Unit (NICU). This study aims to investigate the association between intestinal colonization (IC) by Gram-negative bacteria and the risk of bloodstream infection (BSI) in critically ill neonates. Methods: Data from the electronic medical records of 678 newborns admitted to a NICU Brazilian between 2018 and 2022 were retrospectively analyzed. Participants were monitored by the National Health Security Network. Results: Among neonates, 6.9 % had IC (56.9 % attributed to Acinetobacter baumannii); of these, 19.1 % developed BSI (66.7 % by Staphylococcus spp.). Within the A. baumannii colonization, 34.5 % occurred during an outbreak in September 2021. Colonized individuals had a longer mean length of stay (49.3 ± 26.4 days) and higher mortality rate (12.8 %) compared to non-colonized individuals (22.2 ± 16.9 days; 6.7 %, respectively). Previous use of antimicrobials and invasive devices significantly increased the risk of colonization. Colonization by drug-resistant microorganisms, along with the occurrence of BSI, was associated with increased mortality and reduced survival time. Conclusions: IC contributed to the incidence of BSI, leading to more extended hospital stays and higher mortality rates. Its early detection proved to be essential to identify an outbreak and control the spread of resistant microorganisms within the NICU.